A Comparative Study of Attitudes Towards Bullying and Perception Towards Handling Bullying Among Stakeholders at The International School of Chonburi, Thailand - Dangmaneerat, Laxmi; Eamoraphan, Suwattana (Scholar: Human Sciences, 2019)
This study was conducted to compare the attitudes towards bullying and perception towards handling bullying among stakeholders at the International School of Chonburi, Thailand. There were 4 objectives of this study (1) to identify the attitudes towards bullying; (2) to identify perception towards handling bullying; (3) to determine the significant difference of attitudes towards bullying; and (4) to determine the significant difference of perception towards handling bullying; among stakeholders at the International School of Chonburi, Thailand. Three groups of stakeholders in the study were school personnel, parents and students. Attitudes were determined by three factors (1) perceived seriousness (2) is this bullying? And (3) empathy towards victim. Perception towards handling bullying was determined by 5 different strategies used to handle a bullying situation. The population for this study were 22 school personnel, 37 students and 37 parents. Two questionnaires used were the Bullying Attitude Questionnaire-Modified (BAQ-M) and the Handling Bullying Questionnaire (HBQ). School parent and students indicated very high to the three aspects of attitudes towards bullying; whereas, parents indicated high. All three groups reported that they were likely to handle a bullying situation. The study indicated that there was a significant difference at .05 in the attitudes towards bullying among stakeholders. A Post-Hoc analysis was done to identify the group that was different. The difference in attitude came from the parent group which was different from the other two groups. The study indicated that there was no significant difference at .05 in the perception towards handling bullying.